The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18502/ijph.v48i2.816
|View full text |Cite
|
Sign up to set email alerts
|

Global View of HIV Prevalence in Prisons: A Systematic Review and Meta-Analysis

Abstract: Background: We aimed to estimate the global prevalence of HIV, as well as cross-countries comparison in people who are in prison. Methods: We systematically assessed published studies reporting HIV prevalence among prisoners in the world. We searched international datasets banks, including PubMed, SCOPUS, Cumulative Index to Nursing and ISI web of science along with local databases and included original articles reporting data on the prevalence of HIV from 1980 to 2017. Results: We included 72 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 58 publications
2
21
0
2
Order By: Relevance
“…In 2012, HIV prevalence in prison populations was 41% in South Africa, 28% in Cote d I’voire, 27% in Zambia, and in Zimbabwe it was suggested that more than half of prisoners were HIV infected [ 3 ]. Additionally, a systematic review and meta-analysis of global and cross-country prevalence of HIV among prisoners showed that HIV prevalence was highest in Africa [ 4 ]. Factors believed to be contributing to high HIV prevalence in prisons are overcrowding, limited access to health care, intravenous drug use and unsafe injecting practices, sexual violence, unprotected sex and tattooing [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, HIV prevalence in prison populations was 41% in South Africa, 28% in Cote d I’voire, 27% in Zambia, and in Zimbabwe it was suggested that more than half of prisoners were HIV infected [ 3 ]. Additionally, a systematic review and meta-analysis of global and cross-country prevalence of HIV among prisoners showed that HIV prevalence was highest in Africa [ 4 ]. Factors believed to be contributing to high HIV prevalence in prisons are overcrowding, limited access to health care, intravenous drug use and unsafe injecting practices, sexual violence, unprotected sex and tattooing [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…South and Southeast Asia placed the third rank of the highest HIV/AIDS incidence after the states of sub-Saharan Africa and North Africa in 2012, as 3.9 million people were living with HIV and 270,000 people becoming newly [343]. Interestingly, HIV prevalence among prisoners has been reported to vary between different countries from 0%-2% in Australia to 2% in America, 11% in Latin American countries, 10% in the Middle East, and 20% in African countries [344]. In China, men who have sex with men (MSM) transmission has surpassed both injection drug use and blood donors and has become the major HIV transmission route, rose from 44.3% in 2008 to 63.5% in 2012 and to 71.3% in 2015 in Nanjing [345].…”
Section: Hiv/aidsmentioning
confidence: 99%
“…The prevalence of human immunodeficiency virus (HIV) in prison populations of SSA countries is much higher than in the general population [ 5 – 7 ], with prevalences up to 13 times higher reported in some countries [ 5 ]. In Ethiopia, the prevalence of HIV in prison populations is more than four times higher than in the general population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%